2018
DOI: 10.24272/j.issn.2095-8137.2018.048
|View full text |Cite
|
Sign up to set email alerts
|

Playing it cool: Characterizing social play, bout termination, and candidate play signals of juvenile and infant Tibetan macaques (Macaca thibetana) 

Abstract: Play behaviors and signals during playful interactions with juvenile conspecifics are important for both the social and cognitive development of young animals. The social organization of a species can also influence juvenile social play. We examined the relationships among play behaviors, candidate play signals, and play bout termination in Tibetan macaques (Macaca thibetana) during juvenile and infant social play to characterize the species play style. As Tibetan macaques are despotic and live in groups with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
1
11
1
Order By: Relevance
“…Consistent with Wright et al (2018), polyadic play periods were observed in this group of macaques (four players, n ¼ 66; five players, n ¼ 10) but occurred less frequently than dyadic (n ¼ 628) or triadic (n ¼ 261) interactions; the mean number of players in a play period was 2.44 AE 0.67. Similarly, the total number of players in a play period was significantly correlated with the duration of a period (r ¼ À0.138, p 0.001), indicating that playing with more individuals decreased the duration of play.…”
Section: Number Of Playerssupporting
confidence: 71%
See 4 more Smart Citations
“…Consistent with Wright et al (2018), polyadic play periods were observed in this group of macaques (four players, n ¼ 66; five players, n ¼ 10) but occurred less frequently than dyadic (n ¼ 628) or triadic (n ¼ 261) interactions; the mean number of players in a play period was 2.44 AE 0.67. Similarly, the total number of players in a play period was significantly correlated with the duration of a period (r ¼ À0.138, p 0.001), indicating that playing with more individuals decreased the duration of play.…”
Section: Number Of Playerssupporting
confidence: 71%
“…Having other individuals in proximity to the play bout (an audience) also seems to impact the play signaling of individuals involved, i.e., the data represent a negative parabolic trend. Play signaling in these juveniles increased as the number of audience members increased from zero to two but decreased with additional individuals beyond this threshold suggesting that the communication value of the play signal may degrade as the complexity and size of the play group increases (Wright et al 2018). However, additional comparative research on this topic is necessary.…”
Section: Tibetan Macaquesmentioning
confidence: 94%
See 3 more Smart Citations